Implementación de un software educativo en el fortalecimiento del área lingüística en los niños y niñas de 3 a 4 años del centro infantil Dimonti - Pilco Asadovay, Mellissa Vitoria (2021)
The present research work was carried out in order to implement educational software that complements the teaching-learning process. The software helps students from the Dimonti Children's Center from three to four years old to improve their academic performance and strengthen their knowledge in a more didactic way.This strategy creates a greater interest in the linguistics subject, where the student can recognize the letters provided by the software and mimic its sound. It must have a friendly interface that allows children to interact in an agile way, this development can be manipulated at any time that is required without the need for teachers and their students to be in the same classroom. Methods were used to fulfill the general objective such as: deductive, analytical and statistical, in the same way for the collection of information techniques such as surveys of parents and teachers of the institution were used. In the development of the project, the Java script programming language, Ajax functions and the adobe platform were used that allows combining the design and programming of the different categories such as: vowels, numbers, figures, shapes providing a striking learning environment, the platform MySQL in the database to be able to load the users who will have access to the software by means of a login, this pedagogical tool allows to achieve the objectives set and at the same time obtain efficient results. With the implementation of educational software, it will provide an enhancement in traditional education allowing the use of computers as a didactic tool for teachers and students.